The Role of Urinary Biomarker Levels in Assessing the Presence and Severity of Ureteropelvic Junction Obstruction in Children: A Systematic Review and Meta-Analysis - Abbas Alipour; Hamid Mohammadjafari; Alireza Rafiei; Omolbanin Amjadi (Journal of Pediatrics Review, 2016)
Context: Ureteropelvic junction obstruction (UPJO) is the most common obstructive disease of the urinary tract in infancy and childhood with a prevalence of 15% - 45% in neonates with antenatal hydronephrosis. The diagnosis of UPJO should be confirmed by imaging studies - most of which have a propensity to radiation exposure.